A comparative descriptive analysis of perceived quality of caring attitudes and behaviours between haemodialysis patients and their nurses - Philippe Delmas; Matteo Antonini; Laurent Berthoud; Louise O'Reilly; Chantal Cara; Sylvain Brousseau; Tanja Bellier‐Teichmann; Jean Weidmann; Delphine Roulet‐Schwab; Isabelle Ledoux; Jérôme Pasquier; Evelyne Boillat; et al. (Wiley, 2020)
Abstract Aim Despite its importance in nursing, perceived quality of the nurse-patient relationship has seldom been researched. This study sought to examine and compare the quality of caring attitudes and behaviours as perceived by haemodialysis patients and their nurses. Design This comparative descriptive study involved 140 haemodialysis patients and 101 nurses caring for them in ten haemodialysis units in the French‐speaking part of Switzerland. Methods Participants completed a sociodemographic questionnaire and the Caring Nurse‐Patient Interaction Scale (CNPI‐70). Results Both nurses and patients reported a high frequency of caring attitudes and behaviours. Patients gave higher ratings than nurses did on all the caring dimensions, except spirituality. Implications are discussed.